Perencanaan Usaha Makanan Chick Me Up - Handhini, Ulfah Nur Fajrima; S, Yelli Eka (Jurnal Informatika Ekonomi Bisnis, 2023)
Population growth in Indonesia has increased every year, seen from 2020 to 2021 Indonesia's population has increased by 1.22%. The increase in population is accompanied by an increase in public consumption. Kedai Chick Me Up is a chicken-based fast food product designed to meet people's consumption needs. The objective of this research is to find answers regarding how to plan a Chick Me Up Shop business and how to set a strategy so that you can achieve success in building a Start Up business. The research method used in this study is a qualitative descriptive analysis method with a case study approach. While the data collection technique used is to use primary and secondary data. The operationalization of the variables used is the entrepreneurship criteria method from Timmons. The results of this study succeeded in formulating a statement that the Chick Me Up Kedai business meets the eligibility standards for executing its business activities as a form of business by looking at and assessing the NPV, ROI, and the resulting payback period.